Defoe’s Unchristian Colonel: Captivity Narratives and Resistance to Conversion - Fleming, Catherine (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2021)
Daniel Defoe’s fictional autobiographies often contain a puritanical conversion narrative, but Colonel Jack’s narrator is unique in his problematized relationship to Christian conversion. Alert to the negative implications of mercenary conversion, Defoe presents in Colonel Jack a hero who not only revels in his complex ploys to evade the law, but explicitly rejects conversion to Christianity at several points in the narrative. By reading Colonel Jack alongside narratives of European enslavement and incarceration, I suggest that in this text Defoe deliberately reproduces the form of the popular Barbary captivity narrative. This subgenre of narrative portrays conversion as a force to be resisted, informs Jack’s reluctance to embrace Christianity, and ultimately suggests that living in a Christian nation may actually be a hindrance to conversion, making Catholic South America a milieu more conducive to the protagonist’s religious transformation than Protestant Virginia.